Increasing Returns, Input-Output Linkages, and Technological Leapfrogging - Fredrik Gallo (Lund University, School of Economics and Management, Department of Economics, 2006)
Firms agglomerate in one region due to increasing returns, input-output linkages and transportation costs. In the de-industrialised region factor prices are lower and a new technology may be profitable to adopt in that region instead, inducing a change in the technological leadership. This paper shows that the risk of locking in to an old technology is monotonically increasing in the benefits of agglomeration. Greater incompatibility between technologies also increases the risk of rejecting potentially superior manufacturing processes.
Keywords: F12; F43; O33; 330; agglomeration; lock-in; new economic geography; technological leapfrogging